HUBUNGAN KEKUATAN OTOT LENGAN DAN BAHU DENGAN KEMAMPUAN SERVICE ATAS BOLA VOLI PADA CLUB PUTRA REKITA PT. KTU KECAMATAN KOTO GASIB - Nidia Octaviana; Slamet Slamet; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: Based on the problem found that the volleyball service capacity of 20 students, there are 12 students who are not categorized as good at performing top service. this is because the physical condition of students such as muscle strength in the arms, shoulders and balance is not optimal. The purpose of this research was to determine the relationship between arm and shoulder muscle strength and upper-serve power. The population in this research was all men's volleyball club Rekita PT. KTU Koto Gasib Subdistrict, in total 20 people. This research uses a total sampling technique. The instrument in this research was a growing dynamometer leg and arm power instrument and top service. Based on the analysis of the normality test, the X data gives an LoMaks of 0.180 and a Ltable of 0.190 while the Y variable returns an Lcount of 0.110 and an LoMaks of 0.190, which means that LoMaks <Ltable, then the data will be normal divided. Based on the above analysis requirements test, the hypothesis test using the product moment test on variable X1 against variable Y, namely data 0.987> 0.575 Rcount> R table data. there is significant relationship between arm and shoulder muscle strength and the ability to operate volleyball. at the gentlemen's club Rekita PT. KTU Koto Gasib District.Key Words: Arm and Shoulder Muscle Strength, Top Service, Volleyball